2009
DOI: 10.1371/journal.pone.0005984
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of a Replication-Deficient Intranasal ΔNS1 H5N1 Influenza Vaccine

Abstract: BackgroundWe developed a novel intranasal influenza vaccine approach that is based on the construction of replication-deficient vaccine viruses that lack the entire NS1 gene (ΔNS1 virus). We previously showed that these viruses undergo abortive replication in the respiratory tract of animals. The local release of type I interferons and other cytokines and chemokines in the upper respiratory tract may have a “self-adjuvant effect”, in turn increasing vaccine immunogenicity. As a result, ΔNS1 viruses elicit stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 66 publications
(60 reference statements)
1
50
0
3
Order By: Relevance
“…As for influenza-vaccine production, a high virus yield is a critical factor because it can reduce cost and sustain longer immune protection periods by providing sufficient antigens. 31,32 Importantly, the influenza (H1N1) split vaccine produced a satisfactory effect against influenza-virus infection at the lowest antigen dose tested (the vaccine at a dose of 7.5 mg with Al(OH) 3 and 15 mg of antigen alone were the optimal conditions). The promising results produced in this study concerning the safety and immunogenicity of the influenza H1N1 split vaccine support their careful evaluation in phase-1 clinical trials in humans.…”
Section: Discussionmentioning
confidence: 99%
“…As for influenza-vaccine production, a high virus yield is a critical factor because it can reduce cost and sustain longer immune protection periods by providing sufficient antigens. 31,32 Importantly, the influenza (H1N1) split vaccine produced a satisfactory effect against influenza-virus infection at the lowest antigen dose tested (the vaccine at a dose of 7.5 mg with Al(OH) 3 and 15 mg of antigen alone were the optimal conditions). The promising results produced in this study concerning the safety and immunogenicity of the influenza H1N1 split vaccine support their careful evaluation in phase-1 clinical trials in humans.…”
Section: Discussionmentioning
confidence: 99%
“…All ⌬NS1 reassortant viruses were obtained by reverse genetics solely on Vero cells (10,14,27,34). The internal segments of influenza A viruses were derived from a modified IVR-116 vaccine strain (WHO) containing a deletion of the NS1 gene.…”
Section: Methodsmentioning
confidence: 99%
“…These findings contradict the previous suggestion that the restricted replication of this virus in MDCK cells is primarily due to the inability to inhibit the IFN response. The mutations described may have direct applications, as they, for example, allow the development of delNS1-based viruses with improved replication efficiency, thereby making it possible to produce such a virus in cell lines other than Vero cells (35) or NS1-expressing MDCK cells (46). Moreover, these mutations may be combined with the G3A and C8U mutations in HA vRNA, which increased the HA expression level of a live, attenuated, NS1-truncated influenza vaccine strain (25).…”
Section: Discussionmentioning
confidence: 99%
“…The local release of IFN and other cytokines and chemokines appears to be an excellent adjuvant that enhances production of immunoglobulins and contributes to the activation of dendritic cells required for antigen presentation (22,31). DelNS1 candidate vaccines against influenza A and B viruses have been developed (35,51), and initial trials in humans showed successful induction of antibody responses (48). Apart from the use in vaccines, delNS1 viruses also show potential as oncolytic agents (27) and viral expression vectors (50).…”
mentioning
confidence: 99%